CW-OSL, LM-OSL and TL dating of bricks from Karakorum, Mongolia: insights from TL spectra - Solongo, Saran; Tengis, Saran; Wagner, Günther A.; Hüttel, Hans-Georg (Geochronometria, 2021)
In this study, we present results of luminescence dating using CW-OSL, LM-OSL and TL on heated quartz from the archaeological and historical site in Karakorum - the ancient capital of Mongolia, to test their convergence with the age control in the form of the Karakorum inscription 1346. The TL spectra conducted on quartz from red and grey coloured bricks appeared to be characteristic of the technological origin. Quartz TL from red bricks showed a UV emission band at similar to 360 nm and a strong fast OSL component dominated signal. In contrast, blue emission detected in the TL spectra of grey coloured bricks, resulting possibly in the medium component dominated OSL signal. Finally, OSL and TL results gave dates from 1180 +/- 70 AD to 1360 +/- 70 consistent with the expected ages.
Gesehen am 09.02.2022